"United We Stand Divided We Fall" : Maternal Social Participation and Children's Nutritional Status in Peru - Favara, Marta (World Bank, Washington, DC, 2014)
In previous literature, social capital has been hypothesized as a substitute for other forms of capital, such as physical and human capital. This paper contributes to this literature, studying the association between mothers' access to social capital via participation in community organizations and their children's nutritional status at 1 and 5 years. Using the Peruvian sample of the Young Lives project, this study suggests that, where human capital is scarce, social capital might have important implications for child development. Maternal social capital is positively associated with height at 1 year old for those children whose mothers have no formal education. No significant association is found at 5 years of age.